A density functional theory study on the selective catalytic reduction of NO by NH3 reactivity of α-Fe2O3 (0 0 1) catalyst doped by Mn, Ti, Cr and Ni. (1st May 2020) - Lyu, Zekang; Niu, Shengli; Lu, Chunmei; Zhao, Gaiju; Gong, Zhiqiang; Zhu, Ying
Highlights: Mn, Ti, Cr and Ni dopants can be doped into the top layer of Fe2 O3 supercell. Cr and Ni dopants inhibit the adsorption of NH3 and O2 . Ti dopant inhibits the formation of oxygen vacancy. With the doped of Mn, the adsorption of NH3 and O2 are enhanced and the oxygen vacancy is extremely easy to form. Abstract: The reactivity of the α-Fe2 O3 doped with the first-row transition metal (namely, Mn, Ti, Cr, or Ni) in the ammonia-selective catalytic reduction (NH3 -SCR) for the NO reduction is investigated by the density functional theory calculation in coupled with the correction of the on-site coulomb interaction (DFT + U). The formation ability of the oxygen vacancy (Ov ) and the adsorption capacity of NH3 and O2 on the doped Fe2 O3 (0 0 1) surface, which is responsible for the satisfying catalytic performance in NH3 -SCR, are investigated. All the four dopants can be stably doped into the top layer of the α-Fe2 O3 (0 0 1) supercell, where the Mn or Ti dopant strengthens the Lewis acid sites and the Cr or Ni dopant shows a negative effect. In addition, the iron-based catalyst modified by the Mn dopant has more reactive oxygen and are extremely prone to form surface oxygen defects. In comparison, we are sure that the Mn dopant is able to improve the performance of the α-Fe2 O3 in NH3 -SCR for the NO reduction.